The Impact of Covid-19 Pandemic on the Livestock Subsector - Hamdi Mayulu; Endang Sawitri; Irsan Tricahyadinata (Jurnal Sains dan Kesehatan, 2023)
The Covid-19 pandemic had an impact on human activities and all sectors globally. This study aims to review the impact of the pandemic on livestock products. Furthermore, data were collected from several literature, websites, national, and international news, relevant to current policies and conditions. The impact on the livestock sub-sector is not measured and includes a decrease in purchasing power and demand for livestock products such as meat, milk, and eggs, decreased profitability, hampered distribution of production inputs such as feed and medicine affect the increasing production costs, veterinary services limitation, hinder the livestock animal and product distribution, disruption on marketing and business downturn. Meanwhile, the positive impact is that farmers created an online-based digital innovation, known as e-commerce, involving product marketing, business, and product diversification. The Government also plays a vital role in demand and price stabilization, which ensures the supply chain sustainability of the products. Therefore, the livestock business can keep running sustainably, especially during the pandemic.